Reverse micelle extraction of antibiotics - Mohd. Setapar, Siti Hamidah; Shiew, Wei Lau; Toorisaka, Eiichi; Goto, Masahiro; Furusaki, Shintaro; Mat, Hanapi (Penerbit UTM Press, 2008)
Many biomolecules such as proteins, enzymes and metal ions could be solubilised effectively into the reverse micelle organic solvents. Therefore, this opens the possibility of using the existing liquid-liquid extraction technology and utilizing reverse micelles for large-scale extraction in downstream processing. So far, there has been very limited research on the use of reverse micelle for antibiotics extraction. Thus, an attempt was made to use dioleylphosphoric acid (DOLPA) reverse micelle to extract antibiotics. It was found that pH, surfactant concentration, as well as antibiotic types and concentration have a significant effect on the solubilizing capacity of antibiotics in the DOLPA reverse micelles system. At optimum conditions, about 63 % of penicillin G could be extracted during forward extraction, and 54 % in backward extraction.